EBV-miR-BART7-3p Imposes Stemness in Nasopharyngeal Carcinoma Cells by Suppressing SMAD7 - Cai, Longmei; Long, Yufei; Chong, Tuotuo; Cai, Wenzhi; Tsang, Chi Man; Zhou, Xiaohan; Lin, Yanling; Ding, Tengteng; Zhou, Wenyan; Zhao, Hongli; Chen, Yuxiang; Wang, Jianguo; et al. (Frontiers in Genetics, 2019)
Cancer stem-like cells, possessing "stemness" properties, play crucial roles in progression, metastasis, and drug resistance in various cancers. Viral microRNAs (such as EBV-miR-BART7-3p), as exogenous regulators, have been discovered to regulate malignant progression of nasopharyngeal carcinoma (NPC) before, suggesting a possible role of viral microRNAs in imposing stemness. In this study, we found that EBV-miR-BART7-3p indeed induce stemness of NPC cells. We firstly observed that EBV-miR-BART7-3p increased the percentage of side population cells, the development of tumor spheres, and the expression level of stemness markers in vitro. This viral microRNA also enhanced stem-like or caner-initiating properties of NPC cells in vivo. Secondly, we identified SMAD7 as a novel target gene of EBV-miR-BART7-3p in addition to PTEN gene we previously reported; this viral microRNA suppressed SMAD7, led to activation of TGF-β signaling, and eventually enhanced the stemness of NPC cells. Silencing of SMAD7 resembled the effects generated by EBV-miR-BART7-3p in NPC cells. After reconstitution of SMAD7, EBV-miR-BART7-3p-expressing cells underwent a phenotypic reversion. EBV-positive NPC cells were used to enable experimental validation. Finally, we further discovered that EBV-miR-BART7-3p increased chemo-resistance of NPC in vitro and in vivo, supporting that EBV-miR-BART7-3 resulted in increased stemness of NPC cells and lead to higher drug resistance and cancer recurrence. Overall, this study displays a novel mechanism underlying viral microRNA-associated stemness of NPC cells. This viral microRNA and its associated cellular genes may be potential therapeutic targets for restraining chemo-resistance and cancer recurrence of NPC.